A verb-naming test accurately detects cognitive changes in ALS. Issue 7 (2nd October 2022) - Aiello, Edoardo Nicolò; Pain, Debora; Radici, Alice; Sideri, Riccardo; Marinou Aktipi, Kalliopi; Mora, Gabriele; Luzzatti, Claudio
Abstract: Verb-naming tests were proposed for detecting cognitive impairment in ALS, although statistical evidence on their clinical usefulness is still lacking. A total of 29 ALS patients and 29 demographic-matched healthy controls (HCs) were administered the Action-Verb-Naming Test (AVNT), a standardized picture-naming task of actions. Patients were also administered the Edinburgh Cognitive and Behavioral ALS Screen (ECAS), and classified according to Strong et al. (Amyotrophic lateral sclerosis-frontotemporal spectrum disorder (ALS-FTSD): revised diagnostic criteria. Amyotroph Lateral Scler Frontotemporal Degener. 2017;18:153–4) criteria. The AVNT discriminated ALS patients from HCs ( p  = 0.026) and yielded high accuracy in detecting cognitive impairments among ALS patients (88% of accuracy; sensitivity = 1; specificity = 0.84; PPV = 0.5; NPV = 1; LR+ = 3.83; LR− = 0), as well as a below-cutoff performance on the ECAS (AUC = 0.74). The AVNT was unrelated to other clinical variables, despite being strongly associated with ECAS total, ALS-specific, Language and Executive scores ( rs = 0.65–0.75). These findings show that verb naming is an accurate test to detect domain-specific cognitive changes in ALS patients, regardless of their disease phenotype.